2020
DOI: 10.3390/nu12123812
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Profiling of Commercially Mixed Functional Foods—Effects in Beta-Amyloid Induced Rats Measured Using 1H NMR Spectroscopy

Abstract: Functional foods such as pomegranate, dates and honey were shown by various previous studies to individually have a neuroprotective effect, especially in neurodegenerative disease such as Alzheimer’s disease (AD). In this novel and original study, an 1H NMR spectroscopy tool was used to identify the metabolic neuroprotective mechanism of commercially mixed functional foods (MFF) consisting of pomegranate, dates and honey, in rats injected with amyloid-beta 1-42 (Aβ-42). Forty-five male albino Wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…A total of eight articles were found to use honey or its derivatives as preventive or therapeutic agents via in vivo investigations for various neurodegenerative disorders. Out of these, three in vivo studies [ 35 , 36 , 37 ] investigated the effect of honey on AD, whereas only one in vivo article [ 38 ] investigated the role of honey products on ALS. Mohd Sairazi and his team conducted two in vivo investigations [ 38 , 39 ] on the role of honey in curbing the effect of status epilepticus and other neurodegenerative disorders induced through excitotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of eight articles were found to use honey or its derivatives as preventive or therapeutic agents via in vivo investigations for various neurodegenerative disorders. Out of these, three in vivo studies [ 35 , 36 , 37 ] investigated the effect of honey on AD, whereas only one in vivo article [ 38 ] investigated the role of honey products on ALS. Mohd Sairazi and his team conducted two in vivo investigations [ 38 , 39 ] on the role of honey in curbing the effect of status epilepticus and other neurodegenerative disorders induced through excitotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Rosli et al studied the role of MFF at 4 mL/kg against Aꞵ at 40 μg/200 μL concentration on rats using metabolomic 1H NMR spectroscopy analysis [ 36 ]. Key constituents of the commercial MFF utilized in this research were concoctions of pomegranate, date, and honey [ 36 ]. Twenty-nine metabolites were found in the tested groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, honey supplementation attenuated these detrimental effects suggesting a neuroprotective effect of chronic honey ingestion. Moreover, previous studies on animals reported that intake of honey was beneficial and improved memory loss and cognitive decline caused by different conditions, such as aging, stress, ovariectomy [40][41][42] and neuroinflammation induced by Aβ-42 injection [43]. The beneficial effects of honey on the brain have been associated with the presence of components such as flavonoids and phenolic acids that can improve oxidative stress and oxidative stress-linked effects [17,44,45].…”
Section: Discussionmentioning
confidence: 99%